The Role of Technology in Facilitating the Acquisition of Pragmatic Competence in Online English Language Learning - Mezia Kemala Sari; Yoni, Efri; Ariani, Sri; Syam, Erlinda; Rasyida, Fadila (UIN Salatiga, 2025)
Pragmatic competence refers to the ability to use language appropriately in social contexts, and is an essential part of language learning. This research investigation is focused on how technology can be potent for developing pragmatic competence in the remote learning context through the English teachers and English learners of Muhammadiyah University of West Sumatera. Fifteen purposive sample participants were selected based on their Proficiency level (Intermediate to advanced), Regular use of online learning platforms and diverse cultural backgrounds. This qualitative research conducted Semi-structured interview and Online Forum Analysis as the instruments in collecting data. This research found the roles of technology in facilitation the acquisition of Pragmatic competence in online learning are Creating authentic learning experiences, Providing explicit instruction on pragmatic norms, and Fostering meaningful interaction among learners. By leveraging technology like virtual exchange program, online discussion forum, interactive English language platform, and video conferencing, the online English language teachers can empower learners to develop the pragmatic skills necessary for effective communication in diverse cultural contexts. So, technology can be one of the tool in facilitating the acquisition of pragmatic competence through English language learning that is held online.